Factors Analysis of Acceptance of LMS Applications as A Substitute to Face-To-Face Learning in Higher Education in Distance Education Systems - muhammad Irwan Ardiansyah; Togar Alam Napitupulu (Institute of Computer Science (IOCS), 2022)
This study aims to determine what factors influence the level of acceptance of LMS technology at the Mataram Open University. as we know, the use of the Open University LMS application is intended for students who take part in face-to-face services starting during the covid 19 pandemic. Individuals who do not understand computers or experience computers inevitably have to be able to accept the learning process with the LMS application. In this study, a quantitative approach is used to determine what factors affect the acceptance rate of LMS applications. the basic research model uses the TAM Technology Acceptance Model, and the Structural Equation Model (SEM) to analyze the acceptance of LMS technology by utilizing AMOS as an analytical tool. Questionnaires were distributed online using the Google Form platform for data collection of students throughout NTB with a total of 269 respondents, consisting of students from various study programs and semesters at the Mataram Open University. The results of the analysis showed that four of the nine hypotheses were rejected or not significant and most of the rejected hypotheses were the original TAM variable. From the results of the study, it is known that LMS (PL) training has a significant effect on user confidence in the ability to use the Internet (KM) and ease. confidence in the ability to use the internet (KM) No significant effect on perceived ease (PK). Perception of Comfort (PK) has a significant effect on Attitudes towards Use (SM). Perception of convenience (PK) has a significant effect on perceived benefits (PU) and perceived benefits (PU) have a significant effect on real users (PN).